Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1037/0096-1523.30.1.151
|View full text |Cite
|
Sign up to set email alerts
|

Vowel Duration Affects Visual Word Identification: Evidence That the Mediating Phonology Is Phonetically Informed.

Abstract: What form is the lexical phonology that gives rise to phonological effects in visual lexical decision? The authors explored the hypothesis that beyond phonological contrasts the physical phonetic details of words are included. Three experiments using lexical decision and 1 using naming compared processing times for printed words (e.g., plead and pleat) that differ, when spoken, in vowel length and overall duration. Latencies were longer for long-vowel words than for short-vowel words in lexical decision but no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
53
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 56 publications
7
53
0
Order By: Relevance
“…The acoustic duration of spoken monosyllabic words is longer if the consonant following the vowel is voiced (e.g., / /), rather than voiceless (e.g., / /; see e.g., Port, 1979Port, , 1981. This distinction in phonetic length is manifest in visual recognition as a longer latency to printed words such as plead, relative to printed words such as pleat (Abramson & Goldinger, 1997;Lukatela, Eaton, Sabadini, & Turvey, 2004). Reading a word engages a phonological form that represents not only phonologically significant distinctions of traditional concern, but also physical phonetic details.…”
Section: The General System For Learning and Identifying Wordsmentioning
confidence: 99%
See 1 more Smart Citation
“…The acoustic duration of spoken monosyllabic words is longer if the consonant following the vowel is voiced (e.g., / /), rather than voiceless (e.g., / /; see e.g., Port, 1979Port, , 1981. This distinction in phonetic length is manifest in visual recognition as a longer latency to printed words such as plead, relative to printed words such as pleat (Abramson & Goldinger, 1997;Lukatela, Eaton, Sabadini, & Turvey, 2004). Reading a word engages a phonological form that represents not only phonologically significant distinctions of traditional concern, but also physical phonetic details.…”
Section: The General System For Learning and Identifying Wordsmentioning
confidence: 99%
“…Among contemporary phonologies, the phonology most befitting the latter characterization is gestural or articulatory phonology (Goldstein & Fowler, 2003;Lukatela et al, 2004). The primitives of gestural phonology are gestures and constellations of gestures of the vocal tract, where a gesture is a characteristic movement pattern of vocal tract articulators and a gestural constellation is a small number of potentially overlapping gestures composing an utterance.…”
Section: The General System For Learning and Identifying Wordsmentioning
confidence: 99%
“…Amongst the 108 trials with a nonword target, 72 had a noun prime phonologically related to the target (e.g., bière /bjεr/ "beer" for BIEVE, a nonword whose plausible pronunciation is /bjεv/) and 36 had a phonologically unrelated noun prime (e.g., nymphe /nεf/ "nymph" for REUX, /rø/). The form-related filler trials with a nonword target were included to discourage participants from associating phonological relatedness, present in two thirds of the test trials, with a word response (see Lukatela, Eaton, Sabadini, & Turvey, 2004). In addition to the test and fillers trials, 10 similar practice trials and two warm-up trials were constructed.…”
Section: Methodsmentioning
confidence: 99%
“…This appears to be analogous to effects of vowel articulation duration with alphabetic text. Here, responses to individually presented words and gaze durations during sentence reading (Abramson & Goldinger, 1997;Lukatela et al, 2004; see also Huestegge, 2010) are shorter when a target word's articulation duration was short (Bdeaf^) than when it was long (Bdeal^), which was attributed to the use of speech-like codes for lexical access. Specifically, the generation of a speech-like code for lexical access was assumed to take less time when the vowel duration was short-hence, faster lexical access for words with short vowel durations.…”
Section: Discussionmentioning
confidence: 99%
“…This claim has been referred to as the minimality hypothesis, and classical models of phonological information use-for example, the influential dual-route cascade (DRC) model (Coltheart, Rastle, Perry, Langdon, & Ziegler, 2001)-share this representational assumption. Recent studies have shown, however, that readers of alphabetic languages use relatively detailed articulationspecific features-such as vowel duration, spoken syllable boundaries, and lexical stress-during visual word identification (Abramson & Goldinger, 1997;Ashby, 2006;Ashby & Clifton, 2005;Ashby & Martin, 2008;Ashby & Rayner, 2004;Ashby, Sanders, & Kingston, 2009;Huestegge, 2010;Lukatela, Eaton, Sabadini, & Turvey, 2004;Wheat, Cornelissen, Frost, & Hansen, 2010). Furthermore, recordings of eye movements have shown that relatively detailed suband supraphonemic information can be gleaned from (parafoveally visible) words before they are directly fixated during silent reading (Ashby & Martin, 2008;Ashby & Rayner, 2004).…”
mentioning
confidence: 99%